Web-Based Outgoing Mail Incoming Information System (SMASKE) at LPPL Radio Swiba 96.3 FM - Fatimah Karimatul Azizah; Ari Pantjarani; Chairullah Naury (Politeknik Harapan Bangsa Surakarta, 2023)
LPPL (Local Public Broadcasting Institution) Swiba Karanganyar Public Radio is a broadcasting institution with a mail filing management system that is still done manually using a ledger. The running process has disadvantages because it takes longer in the input process, prone to writing letter data errors. In addition, without a computerized system will require inefficient document storage. The purpose of this study is to design a web-based information system for archiving incoming mail, outgoing mail at LPPL Radio Swiba Karanganyar. The limitations problems that the author discusses in the study are focused on the process of archiving incoming and outgoing letters. The research method that the author uses in developing this system is the Software Development Life Cycle (SDLC) waterfall model. The programming language used is PHP with Laravel framework and MySQL database. This information system that has been designed has a login, display, add, edit, delete, and prints reports data that can increase efficiency and accuracy in a digital mail filing system. Therefore, the web-based information system is expected to help Radio Swiba Karanganyar in managing mail that can be used by employees who have access rights to manage the system so that data storage becomes structured. Keywords: archiving system, computerization, laravel